In vivo Pig-a and micronucleus study of the prototypical aneugen vinblastine sulfate - Avlasevich, Svetlana L. (Environ Mol Mutagen, 2017)
The Pig-a assay is being used in regulatory studies to evaluate the potential of agents to induce somatic cell gene mutations and an OECD test guideline is under development. A working group involved with establishing the guideline recently noted that representative aneugenic agents had not been evaluated, and to help fill this data gap Pig-a mutant phenotype and micronucleated reticulocyte frequencies were measured in an integrated study design to assess the mutagenic and cytogenetic damage responses to vinblastine sulfate exposure. Male Sprague Dawley rats were treated for twenty-eight consecutive days with vinblastine dose levels from 0.0156 to 0.125 mg/kg/day. Micronucleated reticulocyte frequencies in peripheral blood were determined at Days 4 and 29, and mutant cell frequencies were determined at Days −4, 15, 29, and 46. Vinblastine affected reticulocyte frequencies, with reductions noted during the treatment phase and increases observed following cessation of treatment. Micronucleated reticulocyte frequencies were significantly elevated at Day 4 in the high dose group. Although a statistically significant increase in mutant reticulocyte frequencies were found for one dose group at a single time point (Day 46), it was not deemed biologically relevant because there was no analogous finding in mutant RBCs, it occurred at the lowest dose tested, and only 1 rat exceeded an upper bound tolerance interval established with historical negative control rats. Therefore, whereas micronucleus induction reflects vinblastine’s well-established aneugenic effect on hematopoietic cells, the lack of a Pig-a response indicates that this tubulin-binding agent does not cause appreciable mutagenicity in this same cell type.